Pemerolehan Leksikon Ragam Bahasa Gaul pada Aplikasi X - Juciananda Febriamita; Eliza Abelia; Nayla Zahratul Maula; Ita Ita (Lembaga Pengembangan Kinerja Dosen, 2024)
The study used a qualitative descriptive approach method. The purpose of this study was to determine the acquisition of slang lexicon by teenagers on the X application, providing insight into language in the modern era, the role of social media in language development, understanding slang in forming individual and community identities in social media, and understanding rapid language changes due to technological developments. Language variety is a variation of language that differs according to the context of use, including the relationship between the speaker and the listener. Slang, as a form of variation that continues to develop, is heavily influenced by social media, especially the X application (formerly Twitter), which is the main platform for teenagers. Through interactions on social media, users learn and absorb new vocabulary quickly, which shapes their social identity. This study used a qualitative approach to analyze the slang lexicon that appears in the application, finding categories such as abbreviations, foreign words, and phonological changes. Although slang enriches communication, there is a risk of reducing the use of formal language that needs to be balanced with language literacy education.